Environmental management of water resources and hydropower in Brazil - Loureiro, Solange Maria; Pereira, Vera Lucia Duarte do Valle (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The implementation of sustainable development as a paradigm to be conquested, has in getting energy one of the current challenges. Among the forms of energy, electricity is one of the most used considering the potential for improved quality of life that the access to it propitiates. However, generating, transmitting and using electricity causes great social, environmental and/or economic impacts. In Brazil, due to its large hydroelectric potential, the energy matrix is based on hydroelectricity, however, obtaining power through this source can not be considered completely clean and free of any impacts quite the contrary, it causes numerous environmental, social and political problems. In order to promote sustainability, using hydroelectricity to obtain electric energy, you should reconsider how the multiple use of water needs to be managed. Therefore, it is necessary to think about water use in the context of environmental management committed to the use of natural resources, including water resources, that propitiates the promotion of the common good.